Police officers’ attitudes toward the implementation of community-oriented policing in Turkey - Uluturk, Bulent (Crime & delinquency, 2017)
The current study aims to analyze the historical development of community-oriented policing (COP) in Turkey as well as exploring officers’ attitudes toward COP and examining factors related to their attitudes. The current research is based on a survey of 405 Turkish police officers. We focused on officers’ demographic characteristics, work orientation, training, the level of participation in decision-making, and perception toward public as a way of understanding officers’ attitudes toward community policing. Our research suggests that majority of organization members have favorable attitudes toward community policing and support it in general and in their own department. The results indicate a positive relationship between participation in decision-making, service work orientation, officers’ relationships with citizens, and police officers’ attitudes toward community policing. Furthermore, the study assesses the effects of police culture on officers’ attitudes in a highly centralized police agency and discusses the policy implications of our findings.